INNOVATION AS A KEY FACTOR IN THE DEVELOPMENT OF MODERN EDUCATIONAL TECHNOLOGIES (Marketing Journal, 2025)
In the context of the dynamic development of the digital economy and profound transformation of the labor market, the need for the introduction of innovative teaching methods aimed at developing relevant competencies and professional skills in specialists is significantly increasing. The article analyzes modern innovative approaches to teaching, including online courses, virtual and augmented reality technologies, artificial intelligence, as well as practice -oriented methods such as case - study, shadowing, s econdment and buddying. Particular attention is paid to their importance for improving the quality of professional training, successful adaptation of 379 specialists to changes in the work environment and the development of the concept of continuous education.
Keywords: innovation; educational technologies; digital economy; online learning; artificial intelligence; professional training; competencies